Analisis Implementasi Kebijakan Pengurangan Risiko Bencana dalam Perspektif Sistem-Ekologi Sosial - Sagala, Dini Asshaliyah; Wike, Wike; Danar, Oscar Radyan (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2021)
This research aims to reveal the implementation ofÂ Disaster risk reduction (DRR) policy in Jayapura city, Papua Province, Indonesia through the socio-ecological system (SES) perspective. It applies descriptive method and uses qualitative approach, which was intended to explore the information correlated to DRR policy directly from its implementing agency. The result of this study shows that implementation of DRR policy in Jayapura city still need to be developed, although it has positive progress in recent years. In social dimension, it has fulfilled the criteria described in SES concept, however, the result is slightly different in ecological aspect. In ecological aspect, some of implementing agencies still lack of technocratic expert to solve technical problem which ecological aspect. Under this circumstance, the structural coordination among implementing agency is difficult to be performed. Thus, the local major of Jayapura still need to establish an emergencyâ€™s organization due to critical situation.